Biodegradation of nitro-PAHs by multi-trait PGPR strains isolated directly from rhizosphere soil - Bhoirob Gogoi; Nazim Forid Islam; Hemen Sarma (The Microbe)
Nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) are hazardous, persistent organic pollutants widely distributed globally. They significantly threaten environmental health by degrading soil, water, and air quality. Prolonged exposure to nitro-PAHs increases risks for both humans and wildlife, leading to cancer, genetic mutations, endocrine disruption, neurodegenerative disorders, and oxidative stress. This study explored the degradation of nitro-PAHs using two plant growth-promoting rhizobacterial (PGPR) strains, Bacillus cereus BG034 and Bacillus altitudinis BG05, isolated from the rhizosphere of native plants (Cyperus rotundus, Cyperus esculentus, Imperata cylindrica, and Axonopus compressus). A co-inoculum (BGC01) formed from these bacterial strains of Bacillus cereus BG034 and Bacillus altitudinis BG05, demonstrated significant capabilities for degrading nitro-PAHs. After a 72-hour incubation period, BGC01 effectively removed 76.0 % of 1-nitropyrene and 87.2 % of 2-nitrofluorene. Individually, Bacillus cereus BG034 removed 47.8 % of 1-nitropyrene and 59.9 % of 2-nitrofluorene, while Bacillus altitudinis BG05 achieved the removal abilities of 49.0 % and 59.8 %. In addition to their degradation capacity, these bacteria exhibited traits that promote plant growth. These results emphasize the potential of these bacterial strains, particularly in co-inoculum form, as effective agents for nitro-PAH degradation. This study offers an environmentally friendly and cost-effective solution for environmental remediation and highlights the potential use of these bacteria as biofertilizers for sustainable agriculture.